Determination of Immunogenic Relevant Antigens in the Excretory-Secretory (ES) Products and the Lysates of Ascaridia galli Larvae - Y Garadagh; N Hoghooghirad; P Shayan; A Eslami; S Saffi (Iranian Journal of Parasitology, 2008)
Background: Ascaridia galli, the largest nematode of small intestine of birds, especially the native poultry, may give rise to serious illness, pathological defects and economical losses even in modern poultry production systems. Although various measures have been undertaken to vaccinate poultry against A.galli, no satisfactory results were obtained so far. However, there is no report on the efficacy of excretory-secretory (ES) proteins of A.galli larvae in immunization of poultry. Thus, the aim of the present research project was based on the use of the ES products of the larvae, in order to find the protective antigens.